2004
DOI: 10.1038/sj.sc.3101694
|View full text |Cite
|
Sign up to set email alerts
|

Hormone replacement therapy in women with spinal cord injury – a survey with literature review

Abstract: Study design: Postal questionnaire survey. Objective: To examine the current use of hormone replacement therapy (HRT) in a sample of menopausal women with spinal cord injury (SCI). Setting: National Spinal Injuries Centre (NSIC), Stoke Mandeville Hospital, Aylesbury, UK. Method: A postal questionnaire was sent to 94 women from the NSIC patient database who met the study inclusion criteria (wheelchair dependent, aged 49 years and above, last seen or heard from within the last 3 years).Results: A total of 59 val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 84 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…These studies suggest that there is a high prevalence of hypothalamic–pituitary–ovary axis disorders in SCI women, and these disorders may be involved in the pathogenesis of osteoporosis after SCI. It would seem appropriate to recommend hormone replacement therapy (HRT) for short‐term relief of menopausal symptoms, but to consider alternative managements for osteoporosis prevention in women with SCI 134 . However, HRT may result in an increased risk of thromboembolism in postmenopausal women with SCI.…”
Section: Hormonal Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies suggest that there is a high prevalence of hypothalamic–pituitary–ovary axis disorders in SCI women, and these disorders may be involved in the pathogenesis of osteoporosis after SCI. It would seem appropriate to recommend hormone replacement therapy (HRT) for short‐term relief of menopausal symptoms, but to consider alternative managements for osteoporosis prevention in women with SCI 134 . However, HRT may result in an increased risk of thromboembolism in postmenopausal women with SCI.…”
Section: Hormonal Changesmentioning
confidence: 99%
“…It would seem appropriate to recommend hormone replacement therapy (HRT) for short-term relief of menopausal symptoms, but to consider alternative managements for osteoporosis prevention in women with SCI. 134 However, HRT may result in an increased risk of thromboembolism in postmenopausal women with SCI.…”
Section: Effects On Gonadal Functionmentioning
confidence: 99%
“…In a study of 59 perimenopausal women with spinal cord injuries, 11 were currently using HRT, primarily for menopausal symptoms and osteoporosis, and 4 of the 9 women who were premenopausal stated they would consider HRT when the time comes. 64 No studies were found examining how women with other types of disabilities responded to or perceived menopausal recommendations from healthcare providers since the WHI results were publicized, which begs the question: Did women with disabilities, who have interacted with the healthcare system for long periods, respond to the news the same as women without disabilities who may have had fewer interactions with the healthcare system? It would go beyond the findings of this study to make comparisons of this nature; however, the women with disabilities in this study, for example, those with polio and spinal chord injury, have historically had a long history of interacting with a healthcare system that makes decisions using a knowledge base that has changed and, perhaps, contradicted itself over the course of their lives.…”
Section: Discussionmentioning
confidence: 98%
“…This was mainly for treatment of menopausal symptoms and also prevention of osteoporosis. 10 This was published following the publication of the WHI study which may have resulted in further reduction in use of HRT.…”
mentioning
confidence: 99%